THE EFFECT OF PRINCIPAL LEADERSHIP AND INTERPERSONAL COMMUNICATION ON TEACHER PERFORMANCE AT SMAN 18 TANGERANG REGENCY - Ruli Naruliah; Euphrasia Susy Suhendra (Dinasti International Journal of Education Management And Social Science, 2022)
The problems in this research are: (1) is there any influence of principal's leadership on teacher performance at SMAN 18 Tangerang Regency; (2) is there any influence of Interpersonal Communication on teacher performance at SMAN 18 Tangerang Regency; (3) is there any influence of principal leadership and interpersonal communication together on teacher performance at SMAN 18 Tangerang Regency. Based on the theoretical study and the formulation of the problem, hypotheses were made, namely (1) there was a positive and significant influence between the principal's leadership on teacher performance at SMAN 18 Tangerang Regency. (2) there is a positive and significant effect of Interpersonal Communication on teacher performance at SMAN 18 Tangerang Regency. (3) there is a positive and significant influence between the principal's leadership and interpersonal communication together on the performance of teachers at SMAN 18 Tangerang Regency. The aims of this research are: (1) To find out, understand and analyze the influence of principal's leadership on teacher performance at SMAN 18 Tangerang Regency; (2) To find out, understand and analyze the influence of interpersonal communication on teacher performance at SMAN 18 Tangerang Regency; (3) To find out, understand and analyze the magnitude of the influence of the principal's leadership and interpersonal communication together on the work motivation of teachers at SMAN 18 Tangerang Regency. The population in this study were all teachers of SMAN 18 Tangerang Regency, totaling 45 teachers, with a sample of 45 people and using a saturated sampling technique of total population. The method used for data collection is a questionnaire method. The data analysis used was descriptive analysis, prerequisite test and hypothesis testing which included multiple linear regression analysis to determine the effect of teacher working group activities and academic supervision on teacher performance. Data analysis used SPSS 24 for Windows program. The results showed; (1) the tcount value of the principal's leadership variable is 3.105 with a significant level of 0.003 meaning the principal's leadership has a significant effect on teacher performance; 2) the tcount of interpersonal communication is 3.658 with a significant level of 0.001 meaning that the interpersonal communication variable has a significant effect on teacher performance; 3) the F value of the principal's leadership and interpersonal communication on teacher performance is 56.004 with a significant level of 0.000. The test criteria are if Fcount > F table and significant level < 0.05 so it can be concluded that the principal's leadership and interpersonal communication on teacher performance have a significant effect on teacher performance.